Characteristics of total laparoscopic hysterectomy among women with or without previous cesarean section: retrospective analysis - Koroglu, Nadiye (2018)
BACKGROUND: The number of hysterectomized patients with previous cesarean sections (CSs) has in- creased due to increasing CS rates. A previous history of CS has been demonstrated to be an important risk factor for major complications in total laparoscopic hysterectomy. The aim here was to evaluate the major complications and safety of TLH in patients with previous CS. DESIGN AND SETTING: Retrospective analysis in a tertiary-level center. METHODS: The medical records of 504 total laparoscopic hysterectomy patients operated between May 2013 and May 2017 were reviewed retrospectively. Data on age, parity, surgical indications, duration of op- eration, length of hospital stay, histopathological diagnosis and major intra and postoperative complica- tions were gathered. The patients were categorized into two groups according to their CS history, namely those with and those without previous CS. Major complications were defined as the presence of lower urinary tract injury (bladder or ureter injury), enterotomy/colostomy, bowel serosal injury or vascular injury. RESULTS: There was no difference between the groups in terms of parity, duration of operation, hos- pital stay or pre and postoperative hemoglobin levels. The conversion rates to laparotomy in the pre- vious CS and no CS groups were 2% and 1.7%, respectively. The rates of major complications in the previous CS and no CS groups were 5% and 1.3%, respectively, and these results did not differ signifi- cantly (P > 0.05). CONCLUSION: TLH could be performed safely in the previous CS group, since the complication rate was not different from that of the patients without previous CS.